A combined experimental and finite element approach to analyse the fretting mechanism of the head–stem taper junction in total hip replacement. (September 2017) - Bitter, Thom; Khan, Imran; Marriott, Tim; Lovelady, Elaine; Verdonschot, Nico; Janssen, Dennis
Fretting corrosion at the taper interface of modular hip implants has been implicated as a possible cause of implant failure. This study was set up to gain more insight in the taper mechanics that lead to fretting corrosion. The objectives of this study therefore were (1) to select experimental loading conditions to reproduce clinically relevant fretting corrosion features observed in retrieved components, (2) to develop a finite element model consistent with the fretting experiments and (3) to apply more complicated loading conditions of activities of daily living to the finite element model to study the taper mechanics. The experiments showed similar wear patterns on the taper surface as observed in retrievals. The finite element wear score based on Archard's law did not correlate well with the amount of material loss measured in the experiments. However, similar patterns were observed between the simulated micromotions and the experimental wear measurements. Although the finite element model could not be validated, the loading conditions based on activities of daily living demonstrate the importance of assembly load on the wear potential. These findings suggest that finite element models that do not incorporate geometry updates to account for wear loss may not be appropriate to predict wear volumes of taper connections.